(untitled) (Ius Novum, 2021)
The article is of scientific, research-related nature and deals with the notification of a victim, a witness or a police station that a convict has been released from prison, a remand centre or a psychiatric hospital. The main scientific aim was to assess the justification for introducing such an obligation to Penalty Execution Code and appropriateness of determining its premises. The main research theses aim to show that the notification plays an important role in the protection of a victim and a witness and, in case of the notification of a police station, has a significant preventive value. The research findings are original in nature because they concern issues that are seldom discussed in literature. The research is nationwide but may be useful in other countries because it examines an original legal measure. The article is important to science because it contains a deepened dogmatic analysis and a big load of theoretical thought, as well as to the practice as it indicates directions of interpretation of notification premises and other elements of it, and thus can contribute to its uniform application.